Clinical Diagnosis and Management of Squamous Cell Carcinoma - Sundaresan, Sivapatham (IntechOpen, 2023)
Squamous cell carcinoma remains a significant cause of morbidity and mortality. It is a heterogeneous disease with complex molecular abnormalities. Head and neck squamous cell carcinomas (SCC) represent the most frequent human solid tumors and are a major cause of cancer mortality. Highly heterogeneous tumors arise from closely interconnected epithelial cell populations whose intrinsic self-renewal potential is inversely related to the stratified differentiation program. Cancer prevention strategies are theoretically appealing although often difficult to implement, owing to the multifactorial pathogenesis of most cancers. This book focuses on significant variations of squamous cell carcinoma, including squamous cell carcinoma of the vagina, bladder, head and neck.